J‐refocused 1H PRESS DEPT for localized 13C MR Spectroscopy. (25th February 2013) - Chen, X.; Boesiger, P.; Henning, A.
<x xml:space="preserve">Abstract</x> Proton point‐resolved spectroscopy (PRESS) localization has been combined with distortionless enhanced polarization transfer (DEPT) in multinuclear MRS to overcome the signal contamination problem in image‐selected in vivo spectroscopy (ISIS)‐combined DEPT, especially for lipid detection. However, homonuclear proton scalar couplings reduce the DEPT enhancement by modifying the spin coherence distribution under J modulation during proton PRESS localization. Herein, a J‐refocused proton PRESS‐localized DEPT sequence is presented to obtain simultaneously enhanced and localized signals from a large number of metabolites by in vivo13C MRS. The suppression of J modulation during PRESS and the substantial recovery of signal enhancement by J‐refocused PRESS‐localized DEPT were demonstrated theoretically by product operator formalism, numerically by the spin density matrix simulations for different scalar coupling conditions, and experimentally with a glutamate phantom at various TEs, as well as a colza oil phantom. The application of the sequence for localized detection of saturated and unsaturated fatty acids in the calf bone marrow and skeletal muscle of healthy subjects yielded high signal enhancements simultaneously obtained for all components. Copyright © 2013 John Wiley & Sons, Ltd.